Phase behavior modeling of alkyl amine + hydrocarbon and alkyl amine + alcohol systems using a group contribution associating equation of state - Sánchez, Francisco Adrián (2009)
In this work, a group contribution-associating equation of state namely GCA-EoS, is extended to model the phase behavior of alkyl amine + hydrocarbon and alkyl amine + alcohol systems while considering the association of functional groups. A generalized routine has been implemented to quantify the association effects through functional groups with associating sites. The predictions of the model are found in good agreement with experimental data reported in the literature. The model parameters were estimated in the temperature range 218-428 K and pressures up to 735 kPa. © 2009 American Chemical Society.